Improving Metacognitive Ability Through The Reading Questioning Answering (RQA) Model Assisted With Learning Journals in Nonformal Educational Study Programs - Palenti, Citra Dwi; Putra, Ari; Gusti, Ririn (Universitas Negeri Jakarta, 2023)
The important skills identified by UNESCO for the 21st century remain related to the four pillars of education, including: 1) learning to find out, 2) learning to do, 3) learning to be personal), an 4) learning to live together in peace (learning to live together in peace). One of the skills that must be empowered through the learning process in higher education is metacognitive skills. The aim of this research is to increase metacognitive abilities through the Reading Questioning Answering (RQA) model assisted by learning journals in social and development problems courses.